Milano Città d’Acqua, a current discussion related to water heritage recovery - López-Bravo, Celia; Contin, Antonella; Mosquera Adell, Eduardo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Milan has devoted tireless efforts to establish a hydraulic infrastructure network as a connection to other cities, despite settling on an underground water layer, which naturally supplies its inhabitants and farming. Intending to bridge the distance that separated it from the nearest rivers, continuous engineering works allowed it to build, throughout its history, an extensive system of navigable canals. A tremendous technical endeavor for which it earned the name Città dell’acqua -City of water-. Paradoxically, the ideas to remove these anthropogenic waterworks arose as a result of one of its earlier urban development plans, at the end of the 19th century. This article characterizes the city through a chronological journey. It is focused on the region hydrography and the so-called navigli, its main medieval and modern waterworks. The circumstances and urban arguments that led politicians, urban planners and engineers to dispense with these infrastructures after industrialization, coinciding with the development of the first modern sanitary systems and the increase in road traffic against navigation, are exposed below. Based on this, the contribution discusses the current controversy regarding the municipal government proposal to recover the old canal system. Along with other issues present in this city, the project objectives are reviewed both at urban a metropolitan scale.